The values of the rebo wekasan tradition as a source of social studies learning - Nurjaman, Zamzam; Widyanti, Triani; Suherman, Ade; Mulyana, Eldi (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
Environmental-based education at this time has a very important meaning in building students' character, with social studies learning resources that can be used as a medium to internalize the traditional values that exist in the student environment. An educator must also better understand and master the tradition. This study aims to build student character and expand environmental-based social studies learning resources by introducing the values of the rebo wekasan tradition in the learner's environment. This research method is qualitative with interview data collection techniques on community leaders in Singajaya District. The results of this study are the values contained in the rebo wekasan tradition, namely (1) religious values, attitudes closer to God, and tolerant of people with different beliefs; (2) the value of sharing or social care, in the rebo wekasan tradition, the community is required to pray or share with fellow humans even though people have different beliefs; (3) cultural values, the Rebo Wekasan tradition has culture and traditions that are believed by Muslims who carry out various traditions such as drinking isim water, eating dupi (ketupat wrapped in bamboo leaves); and (4) historical value, in the implementation of the rebo wekasan tradition, historical values are always instilled in the congregation to provide positive values from various historical deviations in the rebo wekasan situation.